Workplace social capital and risk of long-term sickness absence. Are associations modified by occupational grade?. (28th January 2016) - Rugulies, Reiner; Hasle, Peter; Pejtersen, Jan Hyld; Aust, Birgit; Bjorner, Jakob Bue
Abstract : Background: Workplace social capital (WSC) is an emerging topic among both work environment professionals and researchers. We examined (i) whether high WSC protected against risk of long-term sickness absence (LTSA) in a random sample of the Danish workforce during a 1-year follow-up and (ii) whether the association of WSC with sickness absence was modified by occupational grade. Methods: We measured WSC by self-report in a cohort of 3075 employees and linked responses to a national register of sickness absence. We calculated hazard ratios (HRs) and 95% confidence intervals (CIs) of onset of LTSA (≥21 days), adjusted for covariates. We stratified analyses by occupational grade and examined if there was an interaction effect of WSC and occupational grade. Results: A one standard deviation higher WSC score predicted a reduced risk of sickness absence after adjustment for sociodemographic variables, prevalent health problems and health behaviours (HR = 0.85, 95% CI = 0.74–0.99). The HR was attenuated and lost statistical significance after further adjustment for occupational grade (HR = 0.90, 95% CI = 0.78–1.04). When stratified by occupational grade, high WSC predicted a decreased risk of sickness absence among higher grade workers (HR = 0.61, 95% CI = 0.44–0.84) but not among lower grade workers (HR = 0.98, 95% CI = 0.83–1.15). The interaction effect of WSC and occupational grade was statistically significant (HR = 0.97, 95% CI = 0.95–0.99). Conclusion: High WSC might reduce risk of LTSA. However, the protective effect appears to be limited to workers of higher occupational grade.